Elaboración de un biopolímero para uso agroindustrial a partir de suero de leche - Espinoza Pérez, Gabriel Armando (2020)
Whey is usually the largest residue of dairy industries, nationwide 1,672,344 liters of whey are generated so this work presents an alternative to this by-product developing a biopolymer for agro-industrial use from whey where the physical chemical and microbiology properties of the biopolymer were evaluated and the cost benefit was assessed. For this, 6 different treatments were determined where the protein concentration and additive ratio was varied, this was obtained by mixing concentrated whey protein, distilled water. gelatin and glycerin by drying in an oven at 65 degrees Celsius for 6 hours in silicone tray physical parameters such as density, thickness, permeability, tension, chemical parameters such as protein, ash, grease and moisture were evaluated, in addition to microbiology tests of total aerobes, total coliforms, molds and yeasts. As a result, it was obtained that the C2A3 sample presented better physical characteristics with a thickness of 0.49 mm, density of 1.07 g / cm3, tension of 2.43 kg, weight increase against water of 0.45 g and increase of surface area of 219 percent. In addition, in chemical tests, an average of 5.9 percent protein, 1.62 percent ashes, 6.14 percent humidity and 2.04 percent fat were obtained. After microbiologically evaluating the biopolymer, it was determined that it is edible. Finally, a cost benefit analysis was performed where a production cost was obtained is 1.74 dollars, the cost of sale to the public being 2.05 dollars obtaining a cost benefit of 1.83 dollars.